2019
DOI: 10.1055/s-0039-1679934
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Oral Anticoagulants (DOACs) in Cirrhosis and Cirrhosis-Associated Portal Vein Thrombosis

Abstract: Direct-acting oral anticoagulants (DOACs) have provided benefit in patients requiring anticoagulation for certain diseases by decreasing the burden of subcutaneous injections and the requirement for frequent monitoring through regular blood tests, to ensure adequacy of the therapeutic doses. Studies have demonstrated DOACs to be as safe, and in some instance safer, compared with traditional anticoagulants in the general population. However, the studies evaluating DOACs excluded patients with cirrhosis, a condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 117 publications
(143 reference statements)
0
43
0
1
Order By: Relevance
“…However, a higher rate of recanalization obtained by DOACs has been reported in only a single study [20]. In addition, the safety of DOACs is unclear in patients with advanced or decompensated cirrhosis [54]. Therefore, such a conclusion needs to be validated by a head-to-head randomized comparison.…”
Section: Discussionmentioning
confidence: 96%
“…However, a higher rate of recanalization obtained by DOACs has been reported in only a single study [20]. In addition, the safety of DOACs is unclear in patients with advanced or decompensated cirrhosis [54]. Therefore, such a conclusion needs to be validated by a head-to-head randomized comparison.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature, the results deriving from DOACs use in SVT are based on limited and case studies in the acute SVT. These studies have shown acceptable safety and efficacy profile also in cirrhotic patients 14‐18 . A randomized trial of rivaroxaban versus warfarin was performed for the acute non‐neoplastic portal vein thrombosis showing a remarkable efficacy and safety of the DOACs in the acute hepatitis C virus‐related PVT 19 .…”
Section: Discussionmentioning
confidence: 99%
“…( 1 ) Direct‐acting oral anticoagulants (DOACs), a newer class of anticoagulants that either directly inhibit the activation of factor Xa (apixaban, betrixaban, endoxaban, and rivaroxaban) or thrombin (dabigatran), have become the most commonly prescribed oral agents to prevent ischemic stroke in AF. ( 6 ) However, registration trials for these agents specifically excluded patients with advanced liver disease because of safety concerns given that all DOACs undergo hepatic metabolism. ( 8 ) Emerging retrospective studies and meta‐analyses generally support the efficacy and safety of both warfarin and DOAC utilization in patients with cirrhosis with AF, ( 9‐12 ) and newer data suggest that DOACs are equally as effective as warfarin at preventing ischemic stroke.…”
mentioning
confidence: 99%